Nongkrong di Kafe Sebagai Perilaku Konsumtif Mahasiswa - Andina, Farah; Zulaikha, Siti (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Hanging out in cafes has become a significant social phenomenon among students, influencing social interactions, identities and lifestyles and encouraging them to emphasize their existence, both in the real world and on social media. The aim of this research is to examine whether students choose cafes over other places, such as facilities, atmosphere or location. This research uses a qualitative approach with descriptive research type. Data collection techniques used participant observation, semi-structured interviews, and documentation. The result of this research reveals that hanging out in cafes is a consumptive behavior for students because it is considered part of a modern lifestyle that supports social status and follows social media trends. By using the theory of consumerism by Jean Baudrillard, which suggests that buying goods by students is no longer a fulfillment of needs, but rather a fulfillment of desires involving signs or symbols in it. This research critically highlights that hanging out in cafes is not only the fulfillment of needs, but also symbolically shapes the lifestyle of students in modern society. In conclusion, the form of consumptive behavior carried out by students in cafes by consuming food and drinks, experiences, facilities in cafes such as sofas, mirrors, wi-fi, air conditioning, spatial concepts and social status associated with these activities makes it a symbolic consumption.